Victim-offender mediation programs: an exploration of practice and theoretical framworks - Gehm, John R. (Western criminology review, 1998)
Victim-offender mediation programs--structured encounters centered around a face-to-face meeting between crime victim and offender--have been the subject of modest but increasing attention. Although considerable variation exists across programs, the common element is a direct voluntary encounter between crime victim and offender. This paper explores what is known from victim-offender mediation research as well as related literature about victim willingness to participate in such meetings and its significance for criminal justice practice. An exploratory framework is suggested, drawing drom restorative justice, equity theory, and narrative theory to stimulate further investigations of this area. Specific research questions and their implications for future research are identified.